PHILOSOPHY OF EDUCATION AND HIGHER SCHOOL - A. I. RAKITOV (Moscow Polytechnic University, 2017)
There is a widely spread opinion, that contemporary higher education experiences a severe crisis, because its educational methods, programs and standards do not correspond to the modern social demands. The structure of developed and developing countries has been changing rapidly under the influence of scientific progress, but the educational standards and programs don't keep up with these changes. To explore the situation and to ground the future changes is the task of philosophy of education. It is necessary to state first of all that the modern society may be called multiple-elite. But all of the elites are grounded on intellectual achievements, which are also multitude. Hence a new task for the modern higher school can be formulated. It should provide this new society of multiple elites with high-skilled and competent specialists. So, the intellectual component of higher education increases significantly. Hence the pressing demand for the penetration in the epistemological structure of higher education.